Asessmen Perkembangan Moral dan Agama di TK IT Darul Fallah Karang Sari, Lampung Tengah - Ningtyas, Anastasya Puspita; Astuti, Luluk Widi; Syahilda, Nurul; Rahma, Aulia (STKIP PGRI Ponorogo Press, 2025)
This research is based on the importance of assessment or the importance of measuring the extent of early childhood moral and religious development. The purpose of this study is to describe how the assessment of moral and religious development at TK IT DARUL FALLAH in Karang Sari. The approach used is qualitative descriptive, with a focus on the moral and religious development of children of the age of dinoi at TK IT DARULL FALLAH in conducting assessments. Data collection techniques use an approach used through observation, in-depth interviews, and documentation. The results of the study showed that out of ten children in TK IT DARULL FALLAH there were eight children who had developed very well and there were two children who had not yet developed., the assessment of moral and religious development was carried out incidentally, the development of moral and religious values at TK IT DARUL FALLAH, Karang Sari, Central Lampung teachers used assessment instruments in the form of checks and anecdotes.